Avaliação da atividade hipoglicemiante do extrato de Myrcia bella em camundongos diabéticos por estreptozotocina - Vareda, Priscilla Maria Ponce [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Diabetes mellitus (DM) is characterized as a metabolic disorder resulting in defects of action and/or insulin secretion, resulting in disturbances in the metabolism of proteins, carbohydrates and lipids which can cause serious consequences to diabetic patients, resulting in complications such as weight loss, increased blood lipid levels, increased incidence of atherosclerosis and peripheral artery diseases, vision and kidneys injury, and in severe cases, death. The incidence of diabetics worldwide is increasing alarming over the years, and recent research has shown that the number of diabetics in the population will tend to a significantly increasing in coming decades. This alarming increase in the incidence of diabetes is due to the current lifestyles including unhealthy habits, sedentary lifestyle and obesity. Current treatments for diabetes include the use of exogenous insulin, as well of oral hypoglycemic agents. However, patients report numerous side effects and discomfort caused by them. Based on this information, the search for new agents that can act to improve diabetes has become the focus of several studies. In this context, the study of medicinal plants that has hypoglycemic effects and that acts in improving the diabetic state coming arousing interest of researchers. Myrtaceae is a botanical family that has many representatives in the Brazilian flora, and thus generates much interest in research on their species. The genus Myrcia is still not well explored by the researchers, and there are a few studies about the hypoglycemic activity of species in that genus. Thus, the aim of this study was to evaluate the possible hypoglycemic activity of the crude extract of the leaves of Myrcia bella Cambess, a plant from the Brazilian cerrado, in streptozotocin-induced diabetic mice. Diabetic (STZ SAL and STZ EXT) and control mice (CTL SAL and CTL EXT) were treated during 21 days with saline and the crude extract of ...

O Diabetes mellitus (DM) é caracterizado como uma desordem metabólica, resultante de defeitos da ação ou secreção na insulina, ou ambos, defeitos estes que levam a alterações no metabolismo de proteínas, carboidratos e lipídios. Tais alterações causam sérias consequências aos pacientes diabéticos, levando a graves complicações como perda de peso, aumento nos níveis lipídios no sangue, aumento da incidência de aterosclerose e doenças arteriais periféricas, danos à visão e aos rins, e em casos mais graves, óbito. A incidência de pessoas diabéticas em todo mundo vem aumentando de modo alarmante ao longo dos anos, e pesquisas recentes têm mostrado que o número de diabéticos na população tende a aumentar cada vez mais nas próximas décadas. Esse preocupante aumento na incidência do diabetes deve-se aos atuais estilos de vida das pessoas, que incluem hábitos não saudáveis, sedentarismo e obesidade. Os tratamentos atuais para o DM incluem a insulinoterapia, assim como o uso de hipoglicemiantes orais. No entanto, são relatados pelos pacientes, inúmeros efeitos colaterais e desconfortos causados pelos mesmos. Partindo dessas informações, a pesquisa por novos agentes que possam agir na melhora do diabetes tornou-se alvo de estudos. Nesse contexto, o estudo de plantas medicinais que possuam efeitos hipoglicemiantes e que atuem na melhora do quadro diabético vem despertado o interesse dos pesquisadores. A família Myrtaceae é uma família botânica com muitos representantes na flora brasileira, e, desse modo, gera muito interesse nas pesquisas a respeito de suas espécies. O gênero Myrcia ainda é pouco explorado pelos pesquisadores, e há um número reduzido de estudos acerca da atividade hipoglicemiante de espécies desse gênero. Desse modo, o objetivo deste trabalho foi o de avaliar a possível atividade hipoglicemiante do extrato bruto das folhas de Myrcia bella Cambess., uma planta proveniente ...
Keywords: Diabetes; Plantas medicinais; Mirtacea; Agentes hipoglicemicos; Camundongo como animal de laboratorio; Myrtaceae